Asset Pricing Puzzles and Incomplete Markets - Chris I. Telmer (Queen's University, Department of Economics, 1991)
An endowment economy with heterogeneous agents and incomplete asset markets is specified, parameterized and solved using a numerical solution algorithm. The model features two types of infinitely lived agents who are endowed with different sources for non-tradable income. Despite not being able to insure against endowment risk, individuals are able to partially diversify away idiosyncratic risk by trading in a limited set of competitive asset markets. Numerical results indicate that the model can account for substantially more of the variability in intertemporal marginal rates of substitution documented by Hensen and Jagannathan (1990) than can models based on a representative agent. In addition, the model can generate a mean risk-free rate of interest smaller than the rate of time preference and potentially account for the so called 'risk-free rate puzzle'.
Keywords: 521; 313; 211; 330; incomplete markets; marginal rate of substitution; risk free rates